DURABLE MECHANICAL CIRCULATION SUPPORT AS AN ALTERNATIVE TO HEART TRANSPLANTATION - S. V. Gautier; G. P. Itkin; A. O. Shevchenko; T. A. Khalilulin; V. A. Kozlov (Вестник трансплантологии и искусственных органов)
In the review a comparative analysis of the treatment of end-stage chronic heart failure using heart transplantation and durable mechanical circulatory is conducted. It shows the main advantages and limitations of heart transplantation and the prospects of application of durable mechanical circulatory support technology. The main directions of this technology, including two-stage heart transplant (bridge to transplant – BTT), assisted circulation for myocardial recovery (bridge to recovery – BTR) and implantation of an auxiliary pump on a regular basis (destination therapy, DT).